Efficient Sleeping Beauty DNA Transposition From DNA Minicircles - Nynne Sharma; Yujia Cai; Rasmus O Bak; Martin R Jakobsen; Lisbeth Dahl Schrøder; Jacob Giehm Mikkelsen (Elsevier, 2013)
DNA transposon-based vectors have emerged as new potential delivery tools in therapeutic gene transfer. Such vectors are now showing promise in hematopoietic stem cells and primary human T cells, and clinical trials with transposon-engineered cells are on the way. However, the use of plasmid DNA as a carrier of the vector raises safety concerns due to the undesirable administration of bacterial sequences. To optimize vectors based on the Sleeping Beauty (SB) DNA transposon for clinical use, we examine here SB transposition from DNA minicircles (MCs) devoid of the bacterial plasmid backbone. Potent DNA transposition, directed by the hyperactive SB100X transposase, is demonstrated from MC donors, and the stable transfection rate is significantly enhanced by expressing the SB100X transposase from MCs. The stable transfection rate is inversely related to the size of circular donor, suggesting that a MC-based SB transposition system benefits primarily from an increased cellular uptake and/or enhanced expression which can be observed with DNA MCs. DNA transposon and transposase MCs are easily produced, are favorable in size, do not carry irrelevant DNA, and are robust substrates for DNA transposition. In accordance, DNA MCs should become a standard source of DNA transposons not only in therapeutic settings but also in the daily use of the SB system.